Dietary fatty acid quality affects systemic parameters and promotes prostatitis and pre-neoplastic lesions - Ferrucci, Danilo; Silva, Silas Pinto; Rocha, Andr; Nascimento, Lucas; Vieira, Andre Schwambach; Taboga, Sebastiao Roberto [UNESP]; Mori, Marcelo; Lenz-Cesar, Carlos; Carvalho, Hernandes F. (Nature Publishing Group, 2019)
Environmental and nutritional factors, including fatty acids (FA), are associated with prostatitis, benign prostate hyperplasia and prostate cancer. We hypothesized that different FA in normolipidic diets (7%) affect prostate physiology, increasing the susceptibility to prostate disorders. Thus, we fed male C57/BL6 mice with normolipidic diets based on linseed oil, soybean oil or lard (varying saturated and unsaturated FA contents and omega-3/omega-6 ratios) for 12 or 32 weeks after weaning and examined structural and functional parameters of the ventral prostate (VP) in the systemic metabolic context. Mongolian gerbils were included because they present a metabolic detour for low water consumption (i.e., oxidize FA to produce metabolic water). A linseed oil-based diet (LO, 67.4% PUFAs, omega-3/omega-6 = 3.70) resulted in a thermogenic profile, while a soybean oil-based diet (SO, 52.7% PUFAs, omega-3/omega-6 = 0.11) increased body growth and adiposity. Mice fed lard (PF, 13.1% PUFA, omega-3/omega-6 = 0.07) depicted a biphasic growth, resulting in decreased adiposity in adulthood. SO and PF resulted in hepatic steatosis and steatohepatitis, respectively. PF and SO increased prostate epithelial volume, and lard resulted in epithelial hyperplasia. Animals in the LO group had smaller prostates with predominant atrophic epithelia and inflammatory loci. Inflammatory cells were frequent in the VP of PF mice (predominantly stromal) and LO mice (predominantly luminal). RNAseq after 12 weeks revealed good predictors of a later-onset inflammation. The transcriptome unveiled ontologies related to ER stress after 32 weeks on PF diets. In conclusion, different FA qualities result in different metabolic phenotypes and differentially impact prostate size, epithelial volume, inflammation and gene expression.